2012
DOI: 10.1158/0008-5472.can-11-4199
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α5β1 Plays a Critical Role in Resistance to Temozolomide by Interfering with the p53 Pathway in High-Grade Glioma

Abstract: Integrins play a role in the resistance of advanced cancers to radiotherapy and chemotherapy. In this study, we show that high expression of the a5 integrin subunit compromises temozolomide-induced tumor suppressor p53 activity in human glioblastoma cells. We found that depletion of the a5 integrin subunit increased p53 activity and temozolomide sensitivity. However, when cells were treated with the p53 activator nutlin-3a, the protective effect of a5 integrin on p53 activation and cell survival was lost. In a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
125
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(141 citation statements)
references
References 25 publications
13
125
1
Order By: Relevance
“…We reasoned that PEA-15 may be one of the links between α5β1 integrin and p53 pathways. Interestingly, similarly to the depletion of α5 integrin, 8 depletion of PEA-15 in U87MG-α5 high cells stabilized and activated p53 (Figure 5a). Addition of Nutlin-3a to siPEA-15 cells significantly enhanced the p53 expression/ phosphorylation compared with control si-nt cells (Figure 5a).…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…We reasoned that PEA-15 may be one of the links between α5β1 integrin and p53 pathways. Interestingly, similarly to the depletion of α5 integrin, 8 depletion of PEA-15 in U87MG-α5 high cells stabilized and activated p53 (Figure 5a). Addition of Nutlin-3a to siPEA-15 cells significantly enhanced the p53 expression/ phosphorylation compared with control si-nt cells (Figure 5a).…”
Section: Resultsmentioning
confidence: 63%
“…We demonstrated that α5β1 integrin interferes with the p53 pathway and that Nutlin-3a (10 μM) represses the α5 integrin subunit through the activation of p53. 8,24 We wondered whether α5 integrin repression would sensitize glioma cells to Nutlin-3a. We treated U87MG cells overexpressing (U87MG-α5 high) or repressed (U87MG-α5 low) for α5 integrin with different doses of Nutlin-3a and evaluated their clonogenic potential.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations